COASTAL COMMUNITY PARTICIPATION IN EFFORTS TO CONSERVE LAKE TONDANO - Towolioe, David; Pioh, Novie R.; Areros, William A. (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract This study aims to analyze and describe Coastal Community Participation in Lake Tondano Preservation Efforts. This research uses a qualitative approach through observation, interviews, document research, primary and secondary data sources, and uses data analysis techniques. The focus of this research utilizes 5 indicators of community participation according to Huraerah. The Minahasa Regency Government seeks to involve local communities through socialization and training in order to achieve effective results in order to preserve Lake Tondano. However, the lack of coordination between the community, village government, and related authorities is still an obstacle. The community also still carries out activities that can unwittingly affect the state and environment around the lake. Although the community has a very good contribution, there needs to be more active awareness in the preservation of Lake Tondano. Minahasa Regency government can facilitate and actively involve the surrounding community in preserving Lake Tondano and also for the local community to be more sensitive to the state of the surrounding environment and more actively participate in contributing to the preservation of Lake Tondano.